DETERMINAN PENGANGGURAN DI INDONESIA: STUDI KASUS DATA IFLS - Astuti, Ismadiyanti Purwaning (Jurnal Ekonomi Pembangunan, 2023)
Unemployment is one of the problems faced by both developed and developing countries. The increasing number of the workforce is not accompanied by an increase in the number of jobs, causing unemployment problems. This study aims to analyze the factors that influence unemployment in Indonesia on a micro basis. These factors include education, gender, and place of residence that affect unemployment in Indonesia. The data used in this study is the 2015 Indonesia Family Life Survey (IFLS) data. The results show that education and residence have a negative and significant effect on unemployment, while gender has a positive and significant impact on unemployment. The education variable shows that individuals who do not attend school are most at risk for unemployment, while individuals with higher education are at least at risk for unemployment. The gender variable shows that male individuals are more at risk for unemployment than women, and individuals who live in rural areas are more at risk of unemployment than those who live in urban areas. From these results, the government must improve the community's education to have the skills to work or create jobs. In addition, the government must equalize educational facilities, not only centered in urban areas but in rural areas necessary to provide adequate educational facilities.